Synthesis Characterization and Study the Antibacterial Activity of Some Transition Metal Complexes of New Thiosemicarbazide Ligand - Khalil, Hussam Mohammed; Hussien , Nasry Jassim (International Journal of Aquatic Research and Environmental Studies, 2026)
N-(2-carbamothioylhydrazine-1-carbonothioyl)-4-methoxybenzamide (L), a new thiosimecarbazide ligand, was prepared and characterised as part of the study. Three coordination were separated from the combination of the title ligand and the metal ions cobalt (II), nickel (II), and copper (II). Using EtOH as the medium, a 1:1 mole ratio of metal to ligand was used to carry out the reaction. The isolated coordination compounds have the following general chemical formula; [LMCl2.H2O)] M(II)= (Co, Ni and Cu). The structural identity of the predicted ligand and its metal complexes have been exhaustively established using various analytical and physico-chemical approaches. These consist of melting point, electronic spectra, FTIR Spectroscopy, and also (1H and 13C) Nuclear Magnetic Resonance spectra. Based on the analytical and spectroscopic data collected, it was found that the synthesized complexes (Co), (Ni) and (Cu) adopted a six-coordinate configuration with a characteristic distorted octahedral environment around the metal center. G+ and G- species antibacterial activity was investigated.